HUBUNGAN PENDEKATAN INKUIRI TERBIMBING MELALUI METODE EKSPERIMEN TERHADAP PENGUASAAN KONSEP KIMIA DAN KREATIVITAS MAHASISWA TEHNIK GEOLOGI UNIVERSITES OTTOW GEISSLER PAPUA - Maulina, Cut; Siregar, Tiurlina (Magister Pendidikan IPA, UNCEN, 2014)
The purpose of the study was to see whether there is a positive and sibnificant relationship between the guided inquiry approach through an experimental method for conceptof chemical, and the creativity of students Department of Geological Engineering University of Ottow Geissler Papua with a samle of 15 people. Data were collected by questionnaire and essay. Data analysis methods used in the research is to use a simple correlation test. From the research that has been done is know that there is a positive and significant relationship between the guided inquiry approach through an experimental method for concept mastery o chemical to the value of 0,9111 count r > rtable 0,514 ; tvalue 7,9713 > ttable 2,160 ; grades rb 0,9532 > rtable 0,532 which means reabel ; X2value 13,4524 < X2table 23,685 which means the data are normally distributed and there is a positive and significant relationship between the gided inquiry approach through experimental methods or student creativity Geological Engineering Prograng at the Unniversity o Papua Geissler Ottow count r value 0,1240 < < rtable 0,514 ; tvalue 0,4533 < 2,160 ; rb value 0,2206 < rtable which means no reabel 0,532 ; X2value 3,6856 < x2table 23,685 which means the data are not normally distributed. Keywords:Guided inquiry, experimental method, concept mastery, creativity.